2014
DOI: 10.1007/s10103-014-1616-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-irradiation with different doses, wavelengths, and application intervals of low-level laser therapy on cytochrome c oxidase activity in intact skeletal muscle of rats

Abstract: Modulation of cytochrome c oxidase activity has been pointed as a possible key mechanism for low-level laser therapy (LLLT) in unhealthy biological tissues. But recent studies by our research group with LLLT in healthy muscles before exercise found delayed skeletal muscle fatigue development and improved biochemical status in muscle tissue. Therefore, the aim of this study was to evaluate effects of different LLLT doses and wavelengths in cytochrome c oxidase activity in intact skeletal muscle. In this animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 56 publications
1
62
0
1
Order By: Relevance
“…33 The simultaneous use of different wavelengths may increase the effects of phototherapy on skeletal muscle performance and may represent a therapeutic advantage in the clinical situations observed in this study and previous studies. 12,24,27,30,31 Finally, our results were due to desirable photobiomodulatory effects of light and not to thermal effects. 26 They were also in line with current evidence that PBMT before exercise has ergogenic effects.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…33 The simultaneous use of different wavelengths may increase the effects of phototherapy on skeletal muscle performance and may represent a therapeutic advantage in the clinical situations observed in this study and previous studies. 12,24,27,30,31 Finally, our results were due to desirable photobiomodulatory effects of light and not to thermal effects. 26 They were also in line with current evidence that PBMT before exercise has ergogenic effects.…”
Section: Discussionmentioning
confidence: 65%
“…Whereas De Marchi et al 23 used 5 diodes of 810-nm infrared laser, we used different light sources simultaneously (4 3 905-nm superpulsed laser, 4 3 875-nm infrared LEDs, and 4 3 640-nm red LEDs) to irradiate our volunteers. Researchers have shown that a combination of different light sources enhances muscular performance, 24,27 decreases pain, 30 increases cytochrome c oxidase activity, 12 decreases fatigue development, and protects muscles against gradually worsening damage. 31 Whereas De Marchi et al 23 reported a difference for oxygen uptake between groups, the clinical importance of these differences remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dose-response of LLLI depends on cell types and illumination parameters such as wavelength, power density, energy density, pulse structure, and treatment timing. [36][37][38] The dose-response effect of the LLLI is biphasic. 24 Lower energy densities of LLLI have a beneficial effect on stimulating and repairing cells and tissues, but higher energy densities have inhibitory effects, such as induction of apoptosis.…”
Section: Figmentioning
confidence: 99%